Remediation of multiple heavy metal-contaminated soil through the combination of soil washing and in situ immobilization - Zhai, Xiuqing; Li, Zhongwu; Huang, Bin; Luo, Ninglin; Huang, Mei; Zhang, Qiu; Zeng, Guangming (The Science of the total environment, 2018)
The remediation of heavy metal-contaminated soils is a great challenge for global environmental sciences and engineering. To control the ecological risks of heavy metal-contaminated soil more effectively, the present study focused on the combination of soil washing (with FeCl3) and in situ immobilization (with lime, biochar, and black carbon). The results showed that the removal rate of Cd, Pb, Zn, and Cu was 62.9%, 52.1%, 30.0%, and 16.7%, respectively, when washed with FeCl3. After the combined remediation (immobilization with 1% (w/w) lime), the contaminated soils showed 36.5%, 73.6%, 70.9%, and 53.4% reductions in the bioavailability of Cd, Cu, Pb, and Zn (extracted with 0.11M acetic acid), respectively, than those of the soils washed with FeCl3 only. However, the immobilization with 1% (w/w) biochar or 1% (w/w) carbon black after washing exhibited low effects on stabilizing the metals. The differences in effects between the immobilization with lime, biochar, and carbon black indicated that the soil pH had a significant influence on the lability of heavy metals during the combined remediation process. The activity of the soil enzymes (urease, sucrase, and catalase) showed that the addition of all the materials, including lime, biochar, and carbon black, exhibited positive effects on microbial remediation after soil washing. Furthermore, lime was the most effective material, indicating that low soil pH and high acid-soluble metal concentrations might restrain the activity of soil enzymes. Soil pH and nutrition were the major considerations for microbial remediation during the combined remediation. These findings suggest that the combination of soil washing and in situ immobilization is an effective method to amend the soils contaminated with multiple heavy metals. [Display omitted] •Soil washing combined with lime addition can effectively amend metal-polluted soil.•pH is a crucial factor to control heavy metal lability in the combined remediation.•Soil enzyme activities are greatly influenced by pH and acid-soluble metal contents.